Using hyperspectral imaging to reveal a hidden precolonial Mesoamerican codex - Snijders, L; Zaman, T; Howell, D (Elsevier, 2016)
Hyperspectral imaging is applied to a Mixtec codex in order to reveal an abundance of never before seen pictographic scenes hidden underneath a layer of gypsum and chalk gesso. Because of the organic nature of these paints, no other technique has been able to reveal them in a non-invasive manner. The results thus far indicate that the covered text contains unique genealogic information which may prove invaluable for the interpretation of archaeological remains from southern Mexico.